PENGARUH SANITASI LINGKUNGAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN KLINIK PRATAMA MEDIKA ANTAPANI - Uci Selawati; Nurul Dwi Ariani (INFOKES (Informasi Kesehatan), 2023)
This study aims to determine the influence of environmental sanitation on employee work productivity ini Klinik Pratama Medika Antapani. The research method used is a quantitative method with a descriptive approach, data collection techniques by distributing questionnaires, observation, and literature review. The sampling technique used saturation sampling with a total of 40 employees as respondents. From the results of the study it can be concluded that the influence of environmental sanitation on work productivity using the spearmen rank correlation test is 77.5%, which means that it has a close relationship and is in a positive direction. The results of the determination test of 67.1% environmental sanitation have a strong relationship to affect employee productivity by 67.1%, the remaining 32.9% is influenced by other factors not examined. The problems that arise include: 1) the cleanliness of the building as a whole is still not maintained in several workspaces, 2) there are several rooms with hot temperatures, 3) there are mosquitoes in the workspace, 4) training during working hours. As for suggestions for fixing the problem: 1) regular discussions with related departments, 2) monitring room temperature supporting facilities, 3) carry out fogging and close the water tank, 4) have replacement employees when there is training. Keywords: environmental sanitation, work productivity